An analysis of the development model for ex-farmworkers and adjacent communities in the Indalo association of private game reserves in the Eastern Cape - Tessendorf, Samantha Millicent (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
Over the past fifteen years there has been an extensive conversion of land use from traditional farming practices to conservation and private game reserves. It has been suggested by Langholz and Kerley (2006:2) that privately owned preserved areas can engage in ecotourism initiatives by protecting biodiversity, succeeding financially and contributing to social upliftment. However, ecotourism has to operate within the context of historical land dispossession of the majority black population and current land reform initiatives to address this problem. In view of the economic, social and environmental importance of ecotourism based private game reserves (PGRs) in South Africa, particularly the Eastern Cape, the main goal of this research is to examine the Indalo association of private game reserves in the Eastern Cape Province's development model for ex-farmworkers and adjacent communities. This was done through a literature survey and analysis of existing studies and by interviewing the managers of the Indalo PGRs and a few farmworkers to get their opinions of the tension between what they are doing and the imperatives of land reform. This involved an exploration of their community development work, particularly around issues of job creation, participation in decision-making, capacity building and sustainability. The thesis comes to the following conclusions. The first is that the establishment of PGRs have a significant positive impact on the local areas in which they are established. As a land-use, ecotourism based game reserves are an economically and ecologically desirable alternative to other land uses. Therefore the ecotourism based private game reserve industry with its extensive community development focus for farmworkers and local communities is a viable and sustainable alternative to conventional land reform. The second is that the Indalo PGRs development work has built capacity in the communities it has served. However, community participation, particularly in decision-making is limited and needs more attention if productive and sustainable development is to be achieved. Lastly, communities rely heavily on external support for their development and upliftment. However, the majority of the PGRs have/or are putting measures in place to ensure the continuation of community development projects to ensure the long-term sustainability of projects.
Keywords: Game reserves -- South Africa -- Eastern Cape; Agricultural laborers -- South Africa -- Eastern Cape; Land reform -- South Africa -- Eastern Cape; Land use -- South Africa -- Eastern Cape; Land use -- Citizen participation; Rural development -- South Africa -- Eastern Cape; Rural development -- Citizen participation